The traveling artist in the Italian Renaissance: geography, mobility, and style - Kim, David Young (Yale Univ. Press, 2014)
"This important and innovative book examines artists' mobility as a critical aspect of Italian Renaissance art. It is well known that many eminent artists such as Cimabue, Giotto, Donatello, Lotto, Michelangelo, Raphael, and Titian traveled. This book is the first to consider the sixteenth-century literary descriptions of their journeys in relation to the larger Renaissance discourse concerning mobility, geography, the act of creation, and selfhood. David Young Kim carefully explores relevant themes in Giorgio Vasari's monumental Lives of the Artists, in particular how style was understood to register an artist's encounter with place. Through new readings of critical ideas, long-standing regional prejudices, and entire biographies, The Traveling Artist in the Italian Renaissance provides a groundbreaking case for the significance of mobility in the interpretation of art and the wider discipline of art history."--Publisher's website